A study on relationship between rewards, organizational commitment, and manager’s attitude on employee loyalty in System Consultancy Services Sdn. Bhd. / Alia Yusrina Alias - Alias, Alia Yusrina (Faculty of Business and Management, 2016)
The long-term success of an organization depends heavily upon the quality of its workers as well as their loyalty towards the organization. A review of literature conducted by previous researches shows that the most often repeated factors of loyalty are motivation, recognition, empowerment, or involvement (Subramani & Krishnaveni, 2009). However, in this study, different dimension will be used to measure the loyalty of employees in an organization, namely rewards, organizational commitment, and manager’s attitude.